Identification of Trichophyton spp. Fungi on Farmers' Toenails in Jagalempeni Village, Brebes Regency - Mohammad Afy Adly; Umi Nihayatul Khusna (Global Writing Academica Researching and Publishing, 2026)
Tinea unguium is a fungal infection caused by dermatophytes and frequently affects individuals in high-risk occupations, such as farmers. Humid working environments, direct contact with soil, and working barefoot increase the risk of fungal nail infections. This study aimed to identify the fungal species causing tinea unguium in the toenails of farmers in Jagalempeni Village, Wanasari District, Brebes Regency, Indonesia. A descriptive cross-sectional study was conducted using 15 toenail scraping specimens cultured on Sabouraud Dextrose Agar (SDA) and identified microscopically with Lactophenol Cotton Blue (LPCB) staining. The results showed the presence of both dermatophyte and non-dermatophyte fungi. Dermatophytes included Trichophyton rubrum (40%) and Trichophyton mentagrophytes (20%), while non-dermatophytes comprised Aspergillus spp. (20%), Rhizopus spp. (13%), and Candida spp. (7%). Trichophyton rubrum was the predominant causative agent. These findings indicate that humid working conditions, prolonged farming activities, and poor foot hygiene may increase the risk of fungal nail infections. Improving personal hygiene and using appropriate protective footwear are recommended to reduce the incidence of tinea unguium among farmers.